Razvoj certificiranja gozdov in tržni vidiki certificiranih lesnih proizvodov - Piškur, Mitja (Gozdarski vestnik, 2011)
The article deals with the development of forest certification and wood tracking, shown primarily on the example of tropical wood use. Understanding the reasons for forest vanishing enables estimating the measures used (once and today) to decrease the scope of deforestation and forest degradation as well as illegal wood trade. Certification levels and their mutual links are presented. Marketing perspectives of the certified wood products are the driving force of expansion of certification among companies and, consequently,forest certification. We indicate direct and indirect positive aspects for certified companies from the viewpoint of ensuring harmony with national and international politics.
Keywords: gozdovi; standardi; certificiranje; sledenje lesa; lesni proizvodi; trg